Analysis of Horticulture Sub-Sector and Fruit Subsector and its Development Strategy in Wonosobo Regency - Yudistira, Rama (Jurnal Indonesia Sosial Sains, 2025)
This research aims to analyze the horticulture and fruit subsectors and formulate development strategies in Wonosobo Regency. The data used in this study are secondary data from 2019-2023. The data analysis methods include Location Quotient (LQ) to identify basic and non-basic commodities and SWOT analysis to develop strategies. The results show that some commodities fall into the basic sector, while others are in the non-basic sector. Development strategies are formulated based on existing strengths, weaknesses, opportunities, and threats to support the optimal development of the horticulture and fruit subsectors in Wonosobo Regency.